The acute effects of static stretching on the sprint performance of collegiate men in the 60- and 100-m dash after a dynamic warm-up - Kistler, B. M; Walsh, M. S; Horn, T. S; Cox, R. H (The Journal of Strength and Conditioning Research, 2010)
Previous research has shown that static stretching has an inhibitory effect on sprinting performances up to 50 m. The purpose of this study was to see what would happen to these effects at longer distances such as those seen in competition. This study used a within-subjects design to investigate the effects of passive static stretching vs. no stretching on the 60- and 100-m sprint performance of college track athletes after a dynamic warm-up. Eighteen male subjects completed both the static stretching and the no stretching conditions in counterbalanced order across 2 days of testing. On each day, all subjects first completed a generalized dynamic warm-up routine that included a self-paced 800-m run, followed by a series of dynamic movements, sprint, and hurdle drills. At the end of this generalized warm-up, athletes were assigned to either a static stretching or a no-stretching condition. They then immediately performed 2 100-m trials with timing gates set up at 20, 40, 60, and 100 m. Results revealed a significant slowing in performance with static stretching (p < 0.039) in the second 20 (20-40) m of the sprint trials. After the first 40 m, static stretching exhibited no additional inhibition of performance in a 100-m sprint. However, although there was no additional time loss, athletes never gained back the time that was originally lost in the first portion of the trials. Therefore, in strict terms of performance, it seems harmful to include static stretching in the warm-up protocol of collegiate male sprinters in distances up to 100 m.